pH-Responsive carriers for oral drug delivery: challenges and opportunities of current platforms - Lin Liu; WenDong Yao; YueFeng Rao; XiaoYang Lu; JianQing Gao (Taylor & Francis Group, 2017)
Oral administration is a desirable alternative of parenteral administration due to the convenience and increased compliance to patients, especially for chronic diseases that require frequent administration. The oral drug delivery is a dynamic research field despite the numerous challenges limiting their effective delivery, such as enzyme degradation, hydrolysis and low permeability of intestinal epithelium in the gastrointestinal (GI) tract. pH-Responsive carriers offer excellent potential as oral therapeutic systems due to enhancing the stability of drug delivery in stomach and achieving controlled release in intestines. This review provides a wide perspective on current status of pH-responsive oral drug delivery systems prepared mainly with organic polymers or inorganic materials, including the strategies used to overcome GI barriers, the challenges in their development and future prospects, with focus on technology trends to improve the bioavailability of orally delivered drugs, the mechanisms of drug release from pH-responsive oral formulations, and their application for drug delivery, such as protein and peptide therapeutics, vaccination, inflammatory bowel disease (IBD) and bacterial infections.